2003
DOI: 10.1063/1.1587878
|View full text |Cite
|
Sign up to set email alerts
|

Dual-mode mechanical resonance of individual ZnO nanobelts

Abstract: The mechanical resonance of a single ZnO nanobelt, induced by an alternative electric field, was studied by in situ transmission electron microscopy. Due to the rectangular cross section of the nanobelt, two fundamental resonance modes have been observed corresponding to two orthogonal transverse vibration directions, showing the versatile applications of nanobelts as nanocantilevers and nanoresonators. The bending modulus of the ZnO nanobelts was measured to be ∼52 GPa and the damping time constant of the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
312
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 494 publications
(324 citation statements)
references
References 19 publications
(15 reference statements)
11
312
0
1
Order By: Relevance
“…For instance, Chen et al [16] showed that the Young' modulus of ZnO nanowire with diameters smaller than about 120 nm is significantly higher than that of bulk ZnO. However, the elastic modulus of vertically aligned [0001] ZnO nanowires with an average diameter of 45 nm measured by atomic force microscopy was found to be far smaller than that of bulk ZnO [17]. The second issue is about the electromechanical coupling in ZnO nanowires.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…For instance, Chen et al [16] showed that the Young' modulus of ZnO nanowire with diameters smaller than about 120 nm is significantly higher than that of bulk ZnO. However, the elastic modulus of vertically aligned [0001] ZnO nanowires with an average diameter of 45 nm measured by atomic force microscopy was found to be far smaller than that of bulk ZnO [17]. The second issue is about the electromechanical coupling in ZnO nanowires.…”
mentioning
confidence: 91%
“…Although many studies on ZnO nanowires have been conducted, there are some important issues remained to be addressed. First, the mechanical properties, especially the Young's modulus of ZnO nanowires are on debate in the literature [16,17,18,19,20]. For instance, Chen et al [16] showed that the Young' modulus of ZnO nanowire with diameters smaller than about 120 nm is significantly higher than that of bulk ZnO.…”
mentioning
confidence: 99%
“…9 The origin of the elastic modulus size dependence has been related to different effects such as the presence of defects 9,11 and the balance between surface and bulk properties as the surface-to-volume ratio varies. 10,12 The elastic properties of ZnO nanostructures and their size dependence have been previously investigated by means of transmission electron microscopy (TEM) 10,13,14 and atomic force microscopy (AFM). 15,16 The Young's modulus of ZnO nanowires was found to decrease dramatically with increasing diameter, reaching the ZnO bulk value for diameters larger than 120 nm.…”
mentioning
confidence: 99%
“…Under ambient conditions, WZ is the most commonly and stable phase of the three. 4 Nowadays, WZ-structured ZnO nanowires are generally synthesized through the solid-vapor phase thermal sublimation technique 5,6 and widely used in the researches of their mechanical properties which are of critical relevance to the design and reliability of devices based on ZnO nanowires.…”
Section: Introductionmentioning
confidence: 99%